Internalisasi Akhlak Esoteris di Pondok Pesantren Al-Shoulatiyah Desa Bargot Topong Kecamatan Padangsidimpuan Batunadua Kota Padangsidimpuan - Handi Wijaya; Muhammad As’adurrofik; Partahian Partahian; Fahrul Harmenedi; Miftah Anugrah Nst (Jurnal Al-Fatih, 2026)
The Qur'an discusses so many moral values in life that it would be very long to explain each of these values comprehensively, among these values is the esoteric value. Esoteric value is a value that perfects human qualities that are exclusive in nature, meaning it is only known and understood by certain people in the inner nature such as behavior and so on. And the tool to understand esoteric values as a counter to the negative impacts of globalization is Islamic religious education (PAI), namely education that is able to prepare creative and productive human resources as well as moral. The research method used is natural field research. The data sources for this study were the leaders, teachers, and students of the Al Shoulatiyah Islamic Boarding School and related documents. The results of this study indicate that four forms of internalization of esoteric morals are; the implementation of PAI learning, the implementation of congregational Dhuhur and Friday prayers, Friday charity, SERBU, and rohis (Islamic Spirituality). The study found that the supporting factors for instilling esoteric values (sincerity and steadfastness) in students at Al Shoulatiyah Islamic Boarding School were self-awareness, resources to support the religious education sector, family environment, and community. Meanwhile, the inhibiting factors for students at Al Shoulatiyah Islamic Boarding School were social interactions between students, limited religious instruction time at school, and negative habits from the family and surrounding community.